Evaluation of a point‐of‐care anticoagulant rodenticide test for dogs. (6th January 2014) - Istvan, Stephanie A.; Marks, Steven L.; Murphy, Lisa A.; Dorman, David C.
Abstract Objective To evaluate a point‐of‐care anticoagulant rodenticide lateral flow analyzer for the detection of various rodenticide compounds. Design Prospective, laboratory study. Setting University teaching hospital. Animals The study utilized a serum sample from one healthy canine donor. Samples were centrifuged and serum samples were aliquoted and either used within 4 hours or frozen at −70°C for further quantitative analysis. Interventions Samples were spiked with clinically relevant concentrations of 1 of 6 rodenticide compounds (warfarin, pindone, chlorphacinone, brodifacoum, bromethalin, and its metabolite desmethylbromethalin). Seventy‐five microliters of spiked serum (or unaltered serum) was introduced into the lateral flow test. Measurements and Main Results Three readers who were blinded to the sample preparation interpreted the lateral flow test as either positive or negative for the presence of anticoagulant rodenticide. All readers were in agreement for the results of each serum sample. The point‐of‐care test kit was able to detect a single anticoagulant rodenticide (warfarin) at concentrations below the manufacturer's recommended limit of detection, but was unable to detect any other anticoagulant rodenticide. Conclusions The results of this test and therapeutic interventions must be considered in light of history, physical examination, and other clinical data. Based on results from this study, the test kit only detects warfarin and not other more common second‐generation anticoagulant rodenticides.